Enrichment of Mobile data Security over Cloud storage using New Asymmetric key algorithm - Kuppuswamy, Prakash (International Journal of Computer Sciences and Engineering, 2025)
Using cloud storage is rapidly increasing at present in all the service and commercial zone. Safety and security concern of the data always uncertain in private, public and hybrid cloud storage system. In particular, mobile data on cloud storage facing enormous challenges and security issues. There is no limitation of mobile users, mobile data and its various services on mobile environment. Increase and deployment of mobile usage much needed to store their vast information in cloud environment, which establish to Mobile data storage on cloud environment. Cloud storage system promotes usage of cloud based services in a mobile environment. Encryption algorithm plays a vital role in securing mobile cloud system in security aspects. The core objective of this paper is to secure the mobile data on cloud environment. In this research article, we comparatively studied and analyzed various encryption algorithms used in mobile cloud base security with proposed new encryption model. Our proposed encryption/decryption method holds the higher security because the more dynamics and randomness are adaptively added into the key generation process with the help of key distribution centre (KDC).